In Silico Function- And Structure-Characterization Of A Hypothetical Protein From Plasmodium Vivax Sal-1 (Applied Biological Research, 2019)
Malaria is a mosquito-borne infectious disease of humans caused by eukaryotic protists of genus Plasmodium. Plasmodium falciparum is mainly  responsible for severe form of malaria while malaria caused by P. vivax, P.  ovale and P. malariae is characteristically milder disease and seldom fatal.  The present study was undertaken to characterize the function and  structure of a hypothetical protein from Plasmodium vivax sal-1 (Accession  No XP-001615924.1) retrieved from NCBI. Different tools and databases  were used to predict the function and structure of this hypothetical protein.  The results showed the presence of Fasciclin 1 domain in the hypothetical  protein. Fasciclin 1domain represents an ancient adhesion domain common  in plants and animals. It is an insect neural cell adhesion molecule involved  in axonal guidance that is attached to the membrane by a GPI-anchored  protein. Results from various in silico studies predicted the role of  hypothetical protein in cell adhesion.
Keywords: Cell adhesion; Fasciclin; hypothetical protein; malaria